PERBEDAAN GAMBARAN ELEKTRODIAGNOSTIK NERVE CONDUCTION STUDY ANTARA NEUROPATHY ASSOCIATED PREDIABETES DAN NEUROPATI DIABETIKA - , Indera; , Prof.Dr.dr. Samekto Wibowo, P.Far.K.,Sp.FK(K),Sp.S(K) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Prediabetes is a transitional stage to DM and plays an important role in the early development of neuropathy. Currently, it is considered that the onset of the neural injury can occur in the initial phase of this metabolic abnormality, during the period of glucose intolerance. The aim of this study was to differentiate the NCS abnormalities in neuropathy associated prediabetes (NAP) and diabetic neuropathy (DN). The design of study was cross sectional. Normoglycemia and glucose intolerance population grouped into prediabetes and DM based on ADA criteria (2012) were recruited in this study. Electrodiagnostic NCS was performed to discover subclinical neuropathy in glucose intolerance population. Parameter medianus MCS, medianus SCS, tibialis MCS and suralis SCS were analysed in 40 normal group, 50 NAP group and 50 DN group. Abnormalities of medianus SCS (distal latency (p=0,044) and distal amplitude (p=0,027)) and suralis SCS (distal latency (p=0,038) and distal amplitude (p<0,001)) were showed in NAP group. Abnormalities of all SCS as well as MCS parameters were showed in DN group (p<0,001). Comparison of NAP and DN group showed statistically significant in all NCS parameters (p<0,05). Multivariate analyses showed SCS suralis reflects earliest alteration in glucose intolerance neuropathy (p<0,001). Sensory abnormality predominant occurs in earliest stage of hyperglycemic state. Axonal degeneration was found more severe instead of demyelination in glucose intolerance neuropathy. In addition, sensory abnormality identified potentially severity in lower extremities.